2012
DOI: 10.1074/jbc.m112.365692
|View full text |Cite
|
Sign up to set email alerts
|

All Human Granzymes Target hnRNP K That Is Essential for Tumor Cell Viability

Abstract: Background: Granzymes have distinct substrate specificities and trigger diverse cell death pathways. Results: All human granzymes can target hnRNP K, which is essential for tumor cell viability. Conclusion: Granzyme-mediated cleavage of hnRNP K contributes to the elimination of tumor cells by cytotoxic lymphocytes. Significance: Elucidating granzyme function provides insights into the role of cytotoxic lymphocytes in tumor immunology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…hn-RNP K is a substrate for granzyme A (GzmA) and caspases and is cleaved during cell death, and its inactivation is a common attribute during apoptosis (32). hnRNP K suppresses apoptosis by suppressing effector caspase-3 and -7 activities by activating caspase inhibitors (33).…”
Section: Resultsmentioning
confidence: 99%
“…hn-RNP K is a substrate for granzyme A (GzmA) and caspases and is cleaved during cell death, and its inactivation is a common attribute during apoptosis (32). hnRNP K suppresses apoptosis by suppressing effector caspase-3 and -7 activities by activating caspase inhibitors (33).…”
Section: Resultsmentioning
confidence: 99%
“…33 Overexpression of an uncleavable NPM mutant, however, fails to protect tumor cells from hGrMinduced cell death. 33 Similarly, knockdown of heterogeneous nuclear ribonucleoprotein K (hnRNP K) -the first substrate known to be cleaved by all five human granzymes -sensitizes tumor cells to LAK-cell-mediated cytotoxicity, 49 and knockdown of survivin, another hGrM substrate, sensitizes tumor cells to hGrM-induced cell death by lowering the threshold for caspase activation. 44 All of these pathways are likely to contribute to hGrM-induced cell death, but none of these appear to be absolutely essential for apoptosis induction.…”
Section: Functionsmentioning
confidence: 99%
“…hn-RNP K plays essential roles in cell survival. Its cleavage by different granzymes initiates cell death processes, and its depletion primes the cells to undergo programmed cell death under various apoptotic stimuli (9,13,41,42). While performing our studies, we observed that VSV-infected cells depleted of hnRNP K exhibited enhanced cytopathic effects and cell death compared to the infected cells not depleted of the protein.…”
Section: Requirement Of Hnrnp K In Vsv Infectionmentioning
confidence: 61%
“…The observation that hnRNP K is highly expressed in multiple cancerous tissues (9)(10)(11)(12) suggests its possible roles in cancer development and tumorigenesis. On the other hand, its sequestration, deficiency, or degradation marks the initial step for apoptotic progression (13)(14)(15).…”
mentioning
confidence: 99%